Islamic Character Education: Mapping and Networking Data Using Bibliometric Analysis - Hanif Cahyo Adi Kistoro; Zamroni; Edi Istiyono; Eva Latipah; Norhapizah Mohd Burhan (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – Character cultivation and development is a major study in modern education today. Islamic character education has become one of the interesting topics in the discussion. This study examines data mapping and networking about Islamic character education in the Scopus journal database. Design/methods/approach – This study used a descriptive qualitative method with a total of 204 selected articles related to Islamic character education. All the published journals have a publication range of the last 13 years, from 2010 to 2023. The authors exported data through software and then processed and analyzed them by using VOSviewer software to find networking maps based on co-author, co-occurrence, and co-citation. Findings – The study results found three significant themes related to the object and results of Islamic character education research, publishers who publish journals, and theoretical citations used by researchers of Islamic character education article journals. Of the three results, the first point related to publication documents is dominated by countries with majority Muslim populations, namely Indonesia and Malaysia. Meanwhile, the second and third points are dominated by Western countries. Another important finding in this study was the keywords found have used many words, such as character education, Islamic education, religion, and Islamic religious education. Research implications/limitations – The results of this study still have limitations on the number of limited publications, subjectivity in analyzing efforts, and incomplete analysis programs. Originality/value – This research can be a reference for future research that is expected to be more comprehensive in designing the research design so as to produce more complete findings.